2003
DOI: 10.1021/es034527y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Oxidation by a Microbial Consortium in a Recirculation Reactor System:  Sulfur Formation under Oxygen Limitation and Removal of Phenols

Abstract: Wastewater from petroleum refining may contain a number of undesirable contaminants including sulfides, phenolic compounds, and ammonia. The concentrations of these compounds must be reduced to acceptable levels before discharge. Sulfur formation and the effect of selected phenolic compounds on the sulfide oxidation were studied in autotrophic aerobic cultures. A recirculation reactor system was implemented to improve the elemental sulfur recovery. The relation between oxygen and sulfide was determined calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
2
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 20 publications
3
38
2
7
Order By: Relevance
“…3). ROS 12 determines the end-products of sulfide oxidation [25,26]. At ROS=1.93, complete sulfide oxidation was observed.…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). ROS 12 determines the end-products of sulfide oxidation [25,26]. At ROS=1.93, complete sulfide oxidation was observed.…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
“…Complicated interactions between different groups of microorganisms can lead to fruitful reactor dynamics [11,13,[25][26][27][28]. Mathematical modeling has been proven to be an effective tool to understand complex biological wastewater treatment processes.…”
Section: Introductionmentioning
confidence: 99%
“…As such, one possible strategy for obtaining the biological oxygen demand required to oxidize hydrogen sulfide to sulfate is to optimize the airto-water oxygen transfer. (2004) studied the relevance of dissolved oxygen in the liquid phase for a bioscrubber to remove hydrogen sulfide at different oxygen/sulfide ratios [9]. Authors observed that at flowrate ratios below 0.5 the hydrogen sulfide oxidation is incomplete producing mainly elemental sulfur.…”
Section: Introductionmentioning
confidence: 99%
“…Um processo interessante para o tratamento do sulfeto é sua oxidação parcial a enxofre elementar, um intermediário insolúvel que pode ser separado e retirado do sistema para reúso (Janssen et al, 1995). O processo de oxidação do sulfeto a enxofre elementar pode ser realizado tanto por via química (Chen e Morris, 1972) quanto por via biológica (Buisman e Lettinga, 1990;Janssen et al, 1999;Alcantara et al, 2004;Kleinjan et al, 2005b), e tem sido reportado por trabalhos que utilizam baixas concentrações de oxigênio (Buisman e Lettinga, 1990;Janssen et al, 1999;Alcantara et al, 2004;Kleinjan et al, 2005b). A manutenção de baixas concentrações de oxigênio no meio justifica-se pela estequiometria da reação (Gijs Kuenen, 1975), segundo a qual, com elevada concentração de oxigênio no meio, o sulfeto pode ser reoxidado a sulfato.…”
Section: Lista De Figurasunclassified
“…Trabalhos têm sido realizados com aeração em um tanque próprio com controle da concentração e posterior injeção do líquido contendo oxigênio dissolvido no reator (Janssen et al, 1998;Janssen et al, 1999;Alcantara et al, 2004;Kleinjan et al, 2005a). Essa técnica evita a turbulência no meio e permite maior controle sobre a dosagem de oxigênio no meio líquido reacional.…”
Section: Lista De Figurasunclassified